Reforming world order through human reformation : a perspective through religion - Kamaruzaman, Kamar Oniah (Kosei Publishing, 2015)
When the modern generation marginalized religion, and in some cases even threw out religion from their lives completely, they therewith also threw out the comprehensive definition of the human being, and with that they lost the comprehensive knowledge of how to live appropriately